Seni Mural Sebagai Media Pendidikan Seni Rupa: Mendorong Kreativitas dan Penyampaian Ekspresi Siswa. - Fahmi, Khairul (JURNAL ILMU PENDIDIKAN, 2024)
Mural analysis as a means of character education at an early age is an effective and creative effort. Murals, paintings or paintings on walls, can teach positive values and character to children. This article outlines how murals can be used in character education, including teaching positive values, providing real examples, developing creativity, strengthening school identity, addressing social problems, and enhancing independence. A mural drawing on the theme "Developing Good Character in a Beautiful World" is presented as an example of visual concepts. The steps of development and implementation of murals, including character values selection, concept design, collaboration with children, and evaluation, are described in detail. Mural evaluation as a character education medium involves observation, child feedback, classroom discussions, interviews with teachers and staff, as well as parental involvement. The evaluation steps include initial target identification, observation of children's actions, safety evaluation and mural care, quotation and description studies, and follow-up to improvements. Periodic evaluation is required to ensure the effectiveness of murals in creating a learning environment that supports the development of positive character of children.